Drivers of audit failure and fraudulent financial reporting: evidence from Nigerian distressed banks / Augustine Ehijeagbon Akhidime - Akhidime, Augustine Ehijeagbon (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2019)
This study examined the drivers (prime facilitators and the motivations) of fraudulent financial reporting and audit failures in distressed Nigerian distressed banks. The study carried out an analytical  review of literature that includes previous empirical studies, reports of investigations of the Nigerian Banks by Financial Regulatory Agencies and  content analysis of the audited financial statements of the distressed banks. The major findings of this study are that the Audit failures that featured in the distressed banks were driven by the overwhelming influence of the board over their auditors. The board through the purchase of their ‘desired’ poor  audit  quality’ at high cost, exposed the auditors to economic bonding  which  compromised their independence and  facilitated  the  issuance of favourable/unqualified  audit opinion on  the board’s fraudulent financial statements that covered up the boards unethical management practices and  material irregularities that undermined the going concern prospects of the banks. The auditors favourable opinions were  proved to be untrue, thus resulting in  Audit failures. The policy  implications of the inferences from this  study is that  the Nigerian legal and  corporate  accounting and auditing  framework  require the  fundamental re-engineering of its rules and structure so as to shield auditors from the undue influence of the  boards, checkmate the excesses of the executive  directors through the upward review of the proportion of non-executive directors on boards, while also  providing  adequate  control over the periodic upward review of audit fees.